The protective role of myeloid-derived suppressor cells in concanavalin A-induced hepatic injury. Issue 9 (1st July 2014) - Diao, Wenli; Jin, Fangfang; Wang, Bing; Zhang, Chen-Yu; Chen, Jiangning; Zen, Ke; Li, Limin
Abstract: The mechanism underlying T cell-mediated fulminant hepatitis is not fully understood. In this study, we investigated whether myeloid derived suppressor cells (MDSCs) could prevent the concanavalin A (ConA)-induced hepatitis through suppressing T cell proliferation. We observed an increase in the frequencies of MDSCs in mouse spleen and liver at early stage of ConA treatment, implicating that the MDSCs might be involved in the initial resistance of mice against ConA-mediated inflammation. Subpopulation analysis showed that the MDSCs in liver of ConA-induced mice were mainly granulocytic MDSCs. Adoptive transfer of the bone marrow-derived MDSCs into ConA-treated mice showed that the MDSCs migrated into the liver and spleen where they suppressed T cell proliferation through ROS pathway. In addition, the frequencies of MDSCs in mice were also significantly increased by the treatment with immune suppressor glucocorticoids. Transfer of MDSCs into the regulatory T cell (Treg)-depleted mice showed that the protective effect of MDSCs on ConA-induced hepatitis is Treg-independent. In conclusion, our results demonstrate that MDSCs possess a direct protective role in T cell-mediated hepatitis, and increasing the frequency of MDSCs by either adoptive transfer or glucocorticoid treatment represents a potential cell-based therapeutic strategy for the acute inflammatory disease.